Structural, optical and electrical impacts of marcasite in pyrite thin films. (1st January 2018) - Moon, Dong Gwon; Rehan, Shanza; Lim, Soo Yeon; Nam, Dahyun; Seo, Ilwan; Gwak, Jihye; Cheong, Hyeonsik; Cho, Yong Soo; Lee, Yunsang; Ahn, SeJin
Graphical abstract: Highlights: In the mixture film, pyrite is surrounded by nanocrystalline marcasite. Marcasite has a bandgap of 0.85 to 0.88 eV, which is not as small as 0.4 eV. Marcasite phase provids an efficient path for diffusion of photogenerated holes. Abstract: The structural and electro-optical influence of marcasite on the properties of solution-processed iron pyrite thin films was investigated. Marcasite has a strong tendency to form simultaneously with pyrite upon sulfurization of amorphous iron-oxide precursor films, leading to a mixed-phase structure in which pyrite grains are surrounded by nanocrystalline marcasite boundaries. The optical analysis in combination with spectroscopic ellipsometry revealed that marcasite should have a bandgap of approximately 0.85–0.88 eV with a higher absorption coefficient than pyrite, differing strongly from the prior belief that marcasite has a bandgap of less than 0.4 eV. In addition, the pyrite/marcasite film has been found to have a larger diffusion coefficient for photogenerated minority carriers than the phase-pure pyrite film from electrochemical impedance analyses, resulting in a higher photocurrent density, as determined through photoelectrochemical measurement. The facile transport of a minority carrier along the marcasite boundaries is the putative origin of the observed improvement in the photoactivity of the pyrite/marcasite mixture films.